SPENDING HABITS OF GEN Z: HOW FINANCIAL LITERACY, LIFESTYLE, AND SELF-CONTROL SHAPE CONSUMER BEHAVIOR IN YOGYAKARTA - Nur Aliza; Tri Harsini Wahyuningsih; Ascariena Rafinda (tesco publisher, 2025)
This study aims to analyze the influence of financial literacy, lifestyle, and self-control on the consumptive behavior of Generation Z in the Special Region of Yogyakarta. A quantitative approach was used, with data collected through an online questionnaire. The respondents consisted of 100 Generation Z individuals residing in the Special Region of Yogyakarta. The data collected were analyzed using multiple linear regression. The results showed that financial literacy has a significant positive effect on consumptive behavior, lifestyle has a significant positive effect on consumptive behavior, while self-control has a significant negative effect on consumptive behavior. The coefficient of determination of 71.6% indicates that these three variables collectively influence the consumptive behavior of Generation Z, while the remaining 28.4% is attributed to other variables not included in this study.